2016
DOI: 10.1158/0008-5472.can-15-2959
|View full text |Cite
|
Sign up to set email alerts
|

mda-7/IL-24 Induces Cell Death in Neuroblastoma through a Novel Mechanism Involving AIF and ATM

Abstract: Advanced stages of neuroblastoma, the most common extracranial malignant solid tumor of the central nervous system in infants and children, are refractive to therapy. Ectopic expression of melanoma differentiation associated gene-7/Interleukin-24 (mda-7/IL-24) promotes broad-spectrum antitumor activity in vitro, in vivo in pre-clinical animal models and in a Phase I clinical trial in patients with advanced cancers, without harming normal cells. mda-7/IL-24 exerts cancer-specific toxicity (apoptosis or toxic au… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 49 publications
(74 reference statements)
0
33
0
1
Order By: Relevance
“…A recent study from our group discovered a novel molecular mechanism of MDA‐7/IL‐24‐mediated cell death in neuroblastoma. Specifically, we found that mda‐7/IL‐24 induces ATM‐mediated activation of H2AX and AIF resulting in caspase‐independent apoptosis that appears unique to neuroblastoma cells (Bhoopathi et al, ). Another recent study from our group demonstrates that overexpression of mda‐7/IL‐24 , either via Ad.…”
Section: Mda‐7/il‐24: Novel Multifunctional Cancer Therapeutic Cytokinementioning
confidence: 93%
See 2 more Smart Citations
“…A recent study from our group discovered a novel molecular mechanism of MDA‐7/IL‐24‐mediated cell death in neuroblastoma. Specifically, we found that mda‐7/IL‐24 induces ATM‐mediated activation of H2AX and AIF resulting in caspase‐independent apoptosis that appears unique to neuroblastoma cells (Bhoopathi et al, ). Another recent study from our group demonstrates that overexpression of mda‐7/IL‐24 , either via Ad.…”
Section: Mda‐7/il‐24: Novel Multifunctional Cancer Therapeutic Cytokinementioning
confidence: 93%
“…We evaluated the therapeutic efficacy of CTV (Ad.PEG‐E1A‐ mda ‐7) in various cancer models including breast, prostate, pancreatic, renal, melanoma, glioma, and neuroblastoma (Azab et al, ; Bhoopathi et al, ; Greco et al, ; Hamed, Das, et al, ; Hamed, Yacoub, et al, ; Sarkar, Su, Vozhilla, Park, Gupta, et al, ; Sarkar et al, ; Sarkar et al, ). Initial studies were performed using the breast cancer model.…”
Section: It Takes More Than Viral Replication Alone To Treat Cancer mentioning
confidence: 99%
See 1 more Smart Citation
“…No significant changes were found between uninfected groups ( Figures 3A1-3A2). A recent study involving a tropism-modified cancer terminator virus (named Ad.5/3-CTV), which selectively replicates in cancer cells producing a robust expression of IL-24 showed induction of apoptosis by modulation of apoptosis-inducing factor (AIF), ATM and g-H2AX (Bhoopathi et al, 2016). A recent study involving a tropism-modified cancer terminator virus (named Ad.5/3-CTV), which selectively replicates in cancer cells producing a robust expression of IL-24 showed induction of apoptosis by modulation of apoptosis-inducing factor (AIF), ATM and g-H2AX (Bhoopathi et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…77 IL-24 kaspazdan bağımsız yolla AIF, ATM ve H2AFX regülasyonu üzerinden nöroblastomda hücre ölü-münü indüklemektedir. 78 Bakiye GÖKER BAĞCA ve ark.…”
Section: Hedefe Yöneli̇k Tedavi̇ Yaklaşimi Ve Gelecek Perspekti̇flerunclassified